(untitled) (Minerva, 2020)
The author of this article suggests the possible relation between the frequent motif of the drunken woman in the art of the Dutch Baroque painter Jan Steen (1626-1679) and a fragment from Ovid’s poetry (ars 3,761-768), where the Roman elegiac poet criticises this kind of behaviour in women.